Global patterns in peatmoss biodiversity - Shaw, A. J. (2014)
DNA sequence data from the nuclear ribosomal internal transcribed spacers (ITS) and the trnL-trnF chloroplast DNA regions were used to quantify geographical partitioning of global biodiversity in peatmosses (Sphagnum), and to compare patterns of molecular diversity with patterns of species richness. Molecular diversity was estimated for boreal, tropical, Neotropical, nonboreal (tropical plus Southern Hemisphere), Old World and New World partitions, based on a total of 436 accessions. Diversity was partitioned among geographical regions in terms of combined nuclear and chloroplast sequence data and separately for the ITS and trnL-trnF data sets.